2014
DOI: 10.1590/0104-1428.1692
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the beta crystalline phase fraction on the mechanical behavior of polypropylene/calcium carbonate/polypropylene - graft - maleic anhydride composites

Abstract: Abstract:The formation of the crystalline phase of polypropylene in the presence of four different types of CaCO 3 was studied. All composites were prepared by melt mixing and extrusion and the concentration of CaCO 3 was maintained at 5 wt %. Furthermore, in another series of composites, 5 wt % of polypropylene-graft-maleic anhydride (PP-g-MA) was added for comparison. The tensile strength, flexural modulus and impact resistance of the composites were determined. The composites were also analyzed by DSC (diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 26 publications
0
15
0
1
Order By: Relevance
“…Thus, the interfacial interaction between the fillers and PP matrix was strengthened, causing the improvement in the mechanical properties. Sakahara et al . found that calcium carbonate/PP composites compatibilized with PP‐g‐MAH showed higher tensile strength, flexural strength, and impact strength, as compared to untreated calcium carbonate/PP composites at corresponding filler content.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Thus, the interfacial interaction between the fillers and PP matrix was strengthened, causing the improvement in the mechanical properties. Sakahara et al . found that calcium carbonate/PP composites compatibilized with PP‐g‐MAH showed higher tensile strength, flexural strength, and impact strength, as compared to untreated calcium carbonate/PP composites at corresponding filler content.…”
Section: Resultsmentioning
confidence: 99%
“…found that calcium carbonate/PP composites compatibilized with PP‐g‐MAH showed higher tensile strength, flexural strength, and impact strength, as compared to untreated calcium carbonate/PP composites at corresponding filler content. Sakahara et al . reported that the addition of 5 wt % calcium carbonate enhanced the tensile strength, flexural modulus, and impact resistance of PP compatibilized with PP‐g‐MAH.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations